Vaccination coverage against human papillomavirus (HPV) and associated factors in female academics from a university in southwestern Goiás, Brazil - Oliveira, Paulo Sérgio de; Gonçalves, Carla Vitola; Watte, Guilherme; Costa, Juvenal Soares Dias da (Revista de Saúde Pública, 2021)
OBJECTIVE To check the coverage of the HPV vaccine in women enrolled in health courses at a university in southwest Goiás, Brazil, and the factors associated with vaccination. METHODS This is a cross-sectional study, including female university students of health courses, aged 18 years or more. A standardized and self-applying questionnaire was used. Participants who received two or more doses of the vaccine were considered immunized. Multiple analysis was performed using multinomial logistic regression. RESULT We observed that, of the 1510 participants, 473 (31.3%) had two or more doses of HPV vaccine, 167 (11.0%) one dose and 870 (57.6%) were unvaccinated. Participants under 21 years of age and in socioeconomic stratum A were 2 times more likely to have received two or more doses of the vaccine (Prevalence Ratio = 1.95; 95%CI 1.40–2.70 and Prevalence Ratio = 2.09; 95%CI 1.39–3.13, respectively). CONCLUSIONS The research revealed extensive possibility for interventions with the aim of achieving greater vaccination coverage among female university students. Even women with more knowledge and high economic stratum showed low vaccination coverage, suggesting that results of higher vaccine coverage can be obtained with vaccination carried out in a school environment.